International Legal Aspects of Human Life Protection in the Process of Application of Innovative Biomedical Technologies - Ostrovska, B.V. (Science and Innovation, 2024)
Introduction. The development of innovative biomedical technologies and the dissemination of biomedical services, as well as the differences in national legislations of the world countries, aggravate the problems in the field of fundamental human rights. The study of international legal regulations for human right to life protection in the context of applying innovative biomedical technologies defines the existence of important and fundamental issues in this sphere, which determines the necessity of their solution based on the international law. Problem Statement. The actual bioethical problems that arise in connection with development of biomedical technologies for human cloning, cryopreservation of cells, tissues, organs, embryos, and human body, human embryonic stem cells, genetic diagnostics, genetic engineering and so on have been considered. Purpose. The purpose of this research is to define the modern threats and challenges to human life in the context of applying the innovative biomedical technologies and their solution based on the international law. Materials and Methods. Based on the dialectical and systematic method, the international legal regulations for innovative application of biomedical technologies in the context to the human right to life have been studied. Results. The analysis of international legal acts and resolutions of the international organizations (the United Nations, the Council of Europe, the European Union) has shown their high effectiveness in terms of solution of the abovementioned problems and further prevention of violations of human right to life, given the development of science and technology. Conclusions. Currently, there is an objective necessity to harmonize the national legislation of different states in the area of human rights and bioethics, as well as to develop general rules of international law of binding character.